Expression of PD‐L1 correlates with pleomorphic morphology and histological patterns of non‐small‐cell lung carcinomas. Issue 6 (5th March 2018) - Ng Kee Kwong, Francois; Laggner, Ute; McKinney, Olivia; Croud, James; Rice, Alexandra; Nicholson, Andrew G
Abstract : Aims: As immunomodulatory therapy is being integrated into treatment regimens for non‐small‐cell lung carcinoma, we aimed to prospectively collect data on the immunohistochemical profile of tumours assessed in our institution and to correlate this with morphological tumour features. Methods and results: Immunohistochemistry for programmed death‐ligand 1 (PD‐L1) was considered to be adequate when >100 tumour cells were seen microscopically. When adequate, PD‐L1 staining was scored as <1%, ≥1–49% or ≥50% positive membrane staining within tumour cells only. There were 197 assessable cases, of which 87% of those with pleomorphic features ( n = 39) showed ≥50% positivity for PD‐L1 expression, as compared with only 33% of cases without pleomorphic features ( P < 0.05) (90% versus 25% in resected cases). Further correlation of PD‐L1 expression with architectural patterns within the tumours was performed in 74 adenocarcinoma resections. All invasive mucinous adenocarcinomas scored <1%. All lepidic components in non‐mucinous adenocarcinoma resections scored <1%. Thirty‐five per cent of the acinar/papillary components and 53% of the solid/micropapillary components were positive for PD‐L1 expression. Conclusions: There are significant differences in PD‐L1 expression in relation to histological patterns, with particularly high levels in those with pleomorphic features and low/undetectable levels in invasive mucinous adenocarcinomas and the lepidic components of non‐mucinous adenocarcinomas. Assessment of PD‐L1 expression in a resected adenocarcinoma with a lepidic component may therefore not be reliable when immumodulatory therapy for recurrent disease is being considered, and either re‐biopsy or limiting assessment to the invasive component may be more appropriate.